The Social Structure of Homicide-Suicide. (November 2015) - Manning, Jason
This article focuses on intimate partner killings to address the question of why some killers subsequently commit suicide whereas others do not. Utilizing Blackian theories of conflict management and Manning's theory of suicide, it advances hypotheses about when intimate partner conflict will result in homicide-suicide rather than homicide alone. These hypotheses propose that differing amounts of status superiority and relational distance predict and explain different patterns of lethal violence. The hypotheses are illustrated and supported with data taken from a study of intimate partner homicides in the state of West Virginia. The article concludes by arguing for a micro-structural model that addresses suicide, homicide, and homicide-suicide.